2018
DOI: 10.1016/j.asmart.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating different closed loop graft preparation technique for tibial suspensory fixation in ACL reconstruction using TightRope™

Abstract: In most anterior cruciate ligament (ACL) reconstructions, grafts are fixed to the femoral side first followed by the tibial side. Various techniques have been reported to achieve optimal tension on the grafts, but once the grafts are fixed it is difficult to adjust graft tension further. To enable post fixation tension control we have invented a new graft configuration using an adjustable loop-device (TightRopeTM, Arthrex, FL, USA) on the tibial side. In this paper, biomechanical properties of this configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We hypothesized that this was mostly due to surgical technique in which grafts were re-tensioned when any laxity was observed arthroscopically after 10 passive flexion-extension knee motions at the final step of the reconstruction. 18 This lessened the initial elongation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We hypothesized that this was mostly due to surgical technique in which grafts were re-tensioned when any laxity was observed arthroscopically after 10 passive flexion-extension knee motions at the final step of the reconstruction. 18 This lessened the initial elongation.…”
Section: Discussionmentioning
confidence: 98%
“…Either EB or TR was used for the femoral fixation device and TR was used as the tibial fixation device in all the cases according to previously reported graft configuration. 18 The initial graft tension was applied manually while arthroscopically verifying the tension of the graft. After the initial fixation of the graft, the knees were passively extended and flexed from 0 to 90° ten times to reveal loss of initial tension that would occur with the beginning of early-phase rehabilitation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the weave of the tendon ends seemed just to take effect of an easy pass through the tunnel and as strings to keep tension. Traditionally, the ends were weaved using the needle suture ( 16 ). However, it was time-consuming, laborious, and required skill.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of the weave, a less time-consuming, simpler, but a firmly fixed method can be used. Sasho et al ( 16 ) tested the mechanical strength of tendon graft samples by employing different suture techniques of joining the two free ends. They found that the ultimate load was the highest in the double zigzag locking loop stitch group (558.7 ± 47.6 N), but a statistically significant difference was not observed among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…While various graft fixation constructs have been studied in depth (Fabbri et al, 2016 ; Lubowitz, 2012 ; Fritsch et al, 2017 ; Sasho et al, 2018 ; Tiefenboeck et al, 2018 ), current biomechanical literature falls short in offering relative comparisons between graft preparation techniques. Although the quadrupled graft preparation technique is the preferred method of graft preparation, multiple techniques have been described (Lubowitz, 2012 ; Fritsch et al, 2017 ; Sasho et al, 2018 ; Tiefenboeck et al, 2018 ; McCarthy et al, 2012 ). Additionally, insufficient tendon length can become a problem for ACL reconstruction in petite patients or in the case of inadvertent amputation of a tendon during harvest, such as in the setting of previous surgery and resultant scar.…”
Section: Introductionmentioning
confidence: 99%